FONEM ANAK: DESAIN PEMEROLEHAN BAHASA PERTAMA (Studi Kasus Tentang Pemerolehan Fonem Anak Pada Periode Praoperasional) - PUTU ADITYA ANTARA (Purwadita : Jurnal Agama dan Budaya, 2017)
This study aims to determine the phoneme acquisition period preoperational child at the  age  of  34  years.  The  subjects  were  children  of  a  family  that  was  in  Rawamangun, Pulo Gadung. The collection of data obtained with longitudinal observations in 2012. The data were analyzed  using  content  analysis  (content  analysis).  The  study  concluded:  1)  Children  aged  3 years and 2 months (ages 34 years) has mastered all vowel phonemes Indonesian. Variations allophonic  also  been  heard.  Phonemes  which  has  been  controlled  children  aged  two  to  three years in terms of phonology show some interesting things. It was found that children aged two to three years are already familiar with the vowel [a], [i] , [u], [e], [o]. 2) Likewise with consonant phonemes, children aged 34 years has been able to say almost all consonant phonemes; like the phoneme / b /, / c /, / d /, / f /, / g /, / h /, / j /, / k /, / l /, / m /, / n /, / p /, / q /, / r /, / s /, / t /, / w /, / y / has sounded clearly in the child’s speech. Of the consonant phonemes that have been heard in the speech of children, there are two phonemes that sound is not too obvious, namely the phoneme / d / and / r /; for the phoneme / r / in so many words actually changed the sound into / l /. 3) There are only three consonant phonemes that do not appear in the speech of children (as in speech context 16 above) that is / v /, / x /, and / z /. Of course, lack the pop three consonant phonemes in the speech of children can not  be  automatically  declared  that  children  of  this  age  can  not  say,  because  by  chance  in  a speech  that  was  taped  there  is  no  word  which  contains  all  three  elements  of  the  consonant phonemes. 4) In the speech of children aged 3ars there is a process monoftongisasi, alteration or  replacement  of  consonant  phonemes,  enforced  disappearances  even  phoneme  syllables.  5) the double consonant phonemes or clusters yet sounds like words / flood / mbah intention, and word / tub / ya mean.